Effect of Tannic Acid and Metallic Mordants on the Dyeing Properties of Natural Dye Extracted from Acacia nilotica Bark - Ali, Asif; Ali, Shaukat; Saleem, Hamna; Hussain, Tanveer (Asian Journal of Chemistry, 2010)
This study is aimed to investigate the effect of tannic acid and metallic mordants on the dyeing properties of natural dye extracted from Acacia nilotica bark. The alkaline extract of the dye was applied on the bleached cotton fabric without and with single and double pre-mordanting. It was found that pre-mordanting with tannic acid, ferrous sulphate, zinc sulphate and aluminum sulphate affect both the colour characteristics and fastness properties of the natural dye. Overall, double mordanting with tannic acid and ferrous sulphate gave the best results in terms of both colour depth and fastness properties.